Object relations, work and the self - Levine, David P. (London Routledge, 2010)
In this book, David P. Levine applies psychoanalytic object relations theory to understanding work motivation and the meaning of work. Drawing on the writings of authors such as Donald Winnicott, Otto Kernberg and Melanie Klein, he explores three factors central to our effort to understand work: guilt, greed and the self. Special attention is paid to the factors that determine the individuals emotional capacity to do work that engages the self and its creative potential and to the related matter of impairment in that capacity. Chapters include:the problem of workgreed, envy and the search for the selfskill, power and authoritywork and reality.Object Relations, Work and the Self will be of interest to psychoanalysts and organizational consultants as well as anyone concerned with what determines the quality of life in the workplace.